2014
DOI: 10.1001/jamainternmed.2014.2356
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative β-Blocker Use in Coronary Artery Bypass Grafting Surgery

Abstract: IMPORTANCE Use of preoperative β-blockers has been associated with a reduction in perioperative mortality for patients undergoing coronary artery bypass grafting (CABG) surgery in observational research studies, which led to the adoption of preoperative β-blocker therapy as a national quality standard.OBJECTIVE To determine whether preoperative β-blocker use within 24 hours of CABG surgery is associated with reduced perioperative mortality in a contemporary sample of patients. DESIGN, SETTING, AND PARTICIPANTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 30 publications
4
50
0
1
Order By: Relevance
“…7,8 Another recently published analysis of the Society of Thoracic Surgeons National Adult Cardiac database assessing the impact of preoperative β-blockers on outcomes in patients undergoing CABG excluded patients with previous MI within 21 days with a consideration that the use of β-blockers is well established after acute MI. 9 Besides, our findings showed that patients with a history of MI shared similar risk of cardiac death (HR, 0.88; 95% CI, 0.59–1.31) and new-onset MI (HR, 1.41; 95% CI, 0.91–2.18) after CABG compared with those without previous MI, indicating the protective impact associated with CABG as a highly sophisticated method of restoring blood flow to the myocardium.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…7,8 Another recently published analysis of the Society of Thoracic Surgeons National Adult Cardiac database assessing the impact of preoperative β-blockers on outcomes in patients undergoing CABG excluded patients with previous MI within 21 days with a consideration that the use of β-blockers is well established after acute MI. 9 Besides, our findings showed that patients with a history of MI shared similar risk of cardiac death (HR, 0.88; 95% CI, 0.59–1.31) and new-onset MI (HR, 1.41; 95% CI, 0.91–2.18) after CABG compared with those without previous MI, indicating the protective impact associated with CABG as a highly sophisticated method of restoring blood flow to the myocardium.…”
Section: Discussionsupporting
confidence: 52%
“…Patients were excluded if they were <18 years of age, had physician-documented contraindications to β-blocker therapy, 9 or underwent CABG combined with valvular or other cardiac surgery. Considering the potential influence of MI history before CABG, this study assessed the use of β-blocker and clinical outcomes in 2 separate cohorts: patients without previous MI and patients with known previous MI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Postoperative postoperative pneumonia, chronic obstructive pulmonary disease and prolonged ventilation periods are also thought to beas important factors in the occurrence of POAF. Although, some studies failed to show the efficacy of preoperative beta blocker use on prevention of POAF, meta-analyses show that beta blockers lower the incidence of POAF and routine use of these agents are suggested by the American Heart Association [8][9][10][11]. Also it is reported in a meta-analysis of twelve clinical trials that preoperative use of statins can decrease incidence of POAF in post-CABG patients [12].…”
Section: Introductionmentioning
confidence: 99%